Atomic love - Fields, Jennie (G.P. Putnam's Sons, 2020)
"Chicago, 1950. Rosalind Porter has always defied expectations--in her work as a physicist on the Manhattan Project and in her passionate love affair with colleague Thomas Weaver. Five years after the end of both, her guilt over the bomb and her heartbreak over Weaver are intertwined. She desperately misses her work in the lab, yet has almost resigned herself to a more conventional life. Then Weaver gets back in touch--and so does the FBI. Special Agent Charlie Szydlo wants Roz to spy on Weaver, whom the FBI suspects of passing nuclear secrets to Russia. Roz helped to develop these secrets and knows better than anyone the devastating power such knowledge holds. But can she spy on a man she still loves, despite her better instincts? At the same time, something about Charlie draws her in. He's a former prisoner of war haunted by his past, just as her past haunts her. As Rosalind's feelings for each man deepen, so too does the danger she finds herself in. She will have to choose: the man who taught her how to love ... or the man her love might save?"--